2004
DOI: 10.1016/j.obhdp.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attribute framing on cognitive processing and evaluation

Abstract: Whereas there is extensive documentation that attribute framing influences the content of people’s thought, we generally know less about how it affects the processes assumed to precede those thoughts. While existing explanations for attribute framing effects rely completely on valence-based associative processing, the results obtained in the present study are also consistent with the notion that negative framing stimulates more effortful and thorough information processing than positive framing. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 64 publications
(94 reference statements)
6
44
1
1
Order By: Relevance
“…First, because negative framing accentuates the possibility of potential losses, and losses are perceived as larger than gains, decision makers might engage in more rigorous and systematic evaluations of detail to avoid a loss or to prevent a potential failure (Tversky and Kahneman, 1981;Dunegan, 1993). Second, because negative information evokes unfavorable associations in memory, and negative moods stimulate more systematic processing, negative framing induces more attention to detail and systematic information processing (Levin, 1987;Levin et al, 1998;Kuvaas and Selart, 2004). Finally, positive incoming information promotes an automatic cognitive mode, which tends to be less thorough and systematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, because negative framing accentuates the possibility of potential losses, and losses are perceived as larger than gains, decision makers might engage in more rigorous and systematic evaluations of detail to avoid a loss or to prevent a potential failure (Tversky and Kahneman, 1981;Dunegan, 1993). Second, because negative information evokes unfavorable associations in memory, and negative moods stimulate more systematic processing, negative framing induces more attention to detail and systematic information processing (Levin, 1987;Levin et al, 1998;Kuvaas and Selart, 2004). Finally, positive incoming information promotes an automatic cognitive mode, which tends to be less thorough and systematic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to affectcognition models and associative effects, people exposed to negatively framed messages that evoke negative emotional states or moods pay more attention to detail and engage in systematic processing. Conversely, people exposed to positively framed messages that evoke positive emotional states or moods engage in a more heuristic processing (Levin, 1987;Levin et al, 1998;Kuvaas and Selart, 2004). Accordingly, the results of Kuvaas and Selart's (2004) experiment showed that decision makers receiving negatively framed information have significantly better recall than those receiving positively framed information; Just and Carpenter's (1976) eye-movement experiment showed that since an implicitly negative sentence is represented as a negation, its presence causes the processing stage to consume extra time.…”
Section: Framing Effect and Cognitive Processingmentioning
confidence: 99%
“…Thus, while it may not encourage risk-taking, negative thinking may facilitate investment of cognitive resources to engage in a complete, analytic diagnosis of the circumstances (Crowe & Higgins, 1997;Dunegan, 1993;Krishnamurthy, Carter, & Blair, 2001). Along similar lines, positive thinking encourages abstract thought while negative thinking facilitates more concrete thought (Kuvaas & Selart, 2004;Tversky & Kahneman, 1986). Therefore, positivity should facilitate thinking about abstract, less predictable elements of problems; for instance, thinking about social elements, values, and purpose .…”
Section: Positive Versus Negative Thinkingmentioning
confidence: 99%
“…Results indicated that when participants were faced with problems that pose explicit opportunities, participants presuppose gains or shift their reference point upward. Kuvaas and Selart (2004) conducted a study where they provided decision makers as leaders with positively or negatively framed information in order to measure recall and confidence in their decisions. Results indicated that individuals in the negative framing condition had better recall than those that received positively framed information.…”
mentioning
confidence: 99%